Current perspectives on tertiary lymphoid structures and PD-1/PD-L1 signaling pathway in the immunotherapy of hepatocellular carcinoma - Hao-Dong QIAO; Yi-Fan LIU; Ze LIANG; Huai-Bin GUO (Yixue xinzhi zazhi)
In the entire world, hepatocellular carcinoma (HCC) is one of the most prevalent cancers. The discovery that HCC is intimately linked to programmed cell death-1 and its ligand (PD-1/PD-L1) in recent years has opened up new possibilities for immunotherapy. However, there are no reliable biomarkers for anti-PD-1/PD-L1 immunotherapy. The latest research has found that tertiary lymphoid structures (TLS) have certain predictive value for the anti PD-1/PD-L1 immunotherapy effect of HCC.This paper analyzes the potential of TLS and PD-1/PD-L1 signaling pathway in hepatocellular carcinoma and covers the mechanism of TLS and PD-1/PD-L1 signaling route, their expression in hepatocellular carcinoma, and particular research developments in the clinic.